Promoting Critical Thinking through the Picha Project - Students’ Experiences - Jamaludin, N.A; Rozzee, I.S.M (INTI International University, 2018)
As stated in the Malaysian Education Blueprint, one of the six primary attributes of student aspirations is promoting students’ critical thinking skills. This attribute appreciates students who have diverse views, are able to think critically and innovatively, have problem solving initiative and an entrepreneurial mindset (Ministry of Education Malaysia, 2015). To meet these goals, an employer-relations project was designed for critical analysis students (CRI2101) with The Picha Project team, a social enterprise, to allow students to get hands-on experience on real-world entrepreneurial struggles. Hence, this research focuses on the impact of employer-relations project in social entrepreneurship on students’ learning. Students’ experience and application of problem solving skills are also observed and measured. A mixed method evidence of students’ experiences was collected from questionnaire, focus group and journal entries, in which the results suggest that The Picha Project gives positive impact to students’ learning. Thus, this paper will provide valuable information for instructors to implement social entrepreneurship projects in classrooms in order to develop critical, innovative and socially responsible students